Linear Modeling of Neurophysiological Responses to Speech and Other Continuous Stimuli: Methodological Considerations for Applied Research - Crosse, Michael J.; Zuk, Nathaniel J.; Di Liberto, Giovanni M.; Nidiffer, Aaron R.; Molholm, Sophie; Lalor, Edmund C. (Frontiers in Neuroscience, 2021)
Cognitive neuroscience has seen an increase in the use of linear modelling techniques for studying the processing of natural, environmental stimuli. The availability of such computational tools has prompted similar investigations in many clinical domains, facilitating the study of cognitive and sensory deficits within an ecologically relevant context. However, studying clinical (and often highly-heterogeneous) cohorts introduces an added layer of complexity to such modelling procedures, leading to an increased risk of improper usage of such techniques and, as a result, inconsistent conclusions. Here, we outline some key methodological considerations for applied research and include worked examples of both simulated and empirical electrophysiological (EEG) data. In particular, we focus on experimental design, data preprocessing and stimulus feature extraction, model design, training and evaluation, and interpretation of model weights. Throughout the paper, we demonstrate how to implement each stage in MATLAB using the mTRF-Toolbox and discuss how to address issues that could arise in applied cognitive neuroscience research. In doing so, we highlight the importance of understanding these more technical points for experimental design and data analysis, and provide a resource for applied and clinical researchers investigating sensory and cognitive processing using ecologically-rich stimuli.